PENGARUH MANAJEMEN KEPENGURUSAN PESANTREN TERHADAP BUDAYA MEMBACA AL- QUR’AN DI PONDOK PESANTREN NURUL HUDA PRINGSEWU : INDONESIA - Nur ?Aida Fitriani; Dwi Rohmadi Mustofa; Muhtarom (LPPM STIT PRINGSEWU, 2020)
ABSTRACT This study aims to determine the effect of boarding school management on al-Qur'an reading culture at nurul huda pringsewu boarding school. This research is a quantitative study by taking samples of 24 female students of second grade B madrasah diniyah nurul huda. Data collection methods in this study are using the method of observation, questionnaires and documentation. In this study, two variables are used, namely management of pesantren management as the dependent variable (X) and the culture of reading al-Qur'an free variables (Y). Analysis of research instruments includes validity and reliability tests. Analysis of the data used is linear analysis. The results of this study indicate that the management of boarding schools in Islamic boarding schools Nurul Huda Pringsewu are in the strong category with a value of. 716 and the culture of reading the Qur'an is in the strong category with tilapia. 747. the results of linear analysis, management of boarding school management to the culture of reading the Koran shows that the significance coefficient value is 0.787 with an alpha value of 0.05. This means that there is a significant influence between the management of the boarding school management on the culture of reading the Qur'an at the boarding school nurul huda pringsewu in the 2016/2017 school year. So, it can be concluded that the management of boarding schools is very influential on the culture of reading the Qur'an. Keywords: boarding school management, al-reading culture The Qur'an ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh manajemen kepengurusan pesantren terhadap budaya membaca al-Qur?an di pondok pesantren nurul huda pringsewu. Penelitian ini merupakan penelitian kuantitatif dengan mengambil sample 24 santri putri kelas dua B madrasah diniyah nurul huda. Metode pengumpulan data dalam penelitian ini adalah menggunakan metode observasi, angket dan dokumentasi. Dalam penelitian ini digunakan dua variabel yaitu manajemen kepengurusan pesantren sebagai variable terikat (X) dan budaya membaca al-Qur?an variable bebas (Y). Analisis instrument penelitian meliputi uji validitas dan reabilitas. Analisis data yang digunakan adalah analisis linier. Hasil penelitian ini menunjukkan bahwa manajemen kepengurusan pesantren di pondok pesantren nurul huda pringsewu berada pada katagori kuat dengan nilai .716 dan budaya membaca al-Qur?an berada pada katagori kuat dengan nila .747. hasil analisis linier, manajemen kepengurusan pesantren terhadap budaya membaca al-Qur?an menunjukkan bahwa nilai koefisien signifikasi 0,787 dengan nilai alpha 0,05. Hal ini berarti ada pengaruh yang signifikan antara manajemen kepengurusan pesantren terhadap budaya membaca al-Qur?an di pondok pesantren nurul huda pringsewu tahun ajaran 2016/2017. Jadi, dapat disimpulkan bahwa manjemen kepengurusan pesantren sangat berpengaruh terhadap budaya membaca al-Qur?an. Kata kunci: manajemen kepengurusan pesantren, budaya membaca al-Qur?an